Strategi Pengembangan Sumber Daya Aparatur pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Nagan Raya - Yoni Meilia; Safrida Safrida (Mahesa Research Center, 2022)
This article or writing aims to find out the development of strategies carried out at the BKPSDM office in Nagan Raya Regency because of obstacles to the enforcement of quality apparatus according to performance achievements. Problems in the development strategy in the form of education and training (training) as well as study permits and learning assignments, where in its implementation there are still obstacles that cause the development strategy has not been implemented optimally. To approach this problem, the theory from Sondang P. Siagian is used which argues that there are several steps that must be achieved in implementing the development strategy. The data was collected through interviews with the secretaries, heads and sub-bids as well as several apparatuses in the BKPSDM office in Nagan Raya Regency and analyzed qualitatively. This study concludes that in implementing the development strategy at the BKPSDM office of Nagan Raya Regency in the form of education and training (education and training) and the provision of learning and learning assignments, several obstacles and shortcomings were found which caused why the apparatus in accordance with performance could not be achieved optimally.